THE PERCEIVED INFLUENCE OF SELF-EFFICACY CONCERNING ORAL PRESENTATIONS - Sirazova , Liliia; Litvinenko, Elena; Toptsi, Jamil (Revista Inclusiones, 2019)
The qualitative study presented in this paper investigates the influence of self-efficacy on oral presentations. Self-efficacy relates to one's beliefs about completing a task successfully and refers to actions, effort, and achievements involved in this process. The current research focuses on two major steps towards understanding oral presentations delivered by international students in Budapest: the first step involves identifying the strengths and weaknesses in the preparation process while the second step defines strengths and weaknesses in the actual delivery of oral presentations. Thirty seven international students from an English-medium program at a University were asked to write a short one-paragraph essay of 120 words in English answering two questions. The dominant emerging themes are examined with the help of qualitative content analysis. The results indicate that student’s self-efficacy beliefs successfully impact their oral performance. Basic elements of presentations such as organization, content, accuracy, appropriateness of language, body language, and engagement with the audience characterize the self-efficacy beliefs of university students concerning the delivery of oral presentations. Overall, results showed that students use learned skills to increase self-efficacy levels in both the preparation and the delivery of oral presentation.